Literature Study: Financial Literacy Encourages the Sustainability of MSMEs? The Perspective of Knowledge Based View (KBV) - Sarsiti, (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
There is currently discussion about the contribution of knowledge-based resources to the sustainability of small and medium-sized Micro, Small, and Medium Enterprises (MSMEs). It has been determined that financial literacy is crucial as a source of information for making financial decisions. Nonetheless, the impact of MSMEs' financial literacy on their sustainability is not sufficiently addressed. From a knowledge-based standpoint, MSMEs can sustain their performance with the aid of knowledge resources including financial literacy and business experience. Positive findings from the study indicate that financial literacy affects MSMEs' success. The disparities in research findings can be attributed to both cultural differences and the absence of assessment standards for financial literacy. This is confirmed that the financial literacy of MSME owners is a key untapped organizational resource that can improve MSME performance (Growth) through sustainable competitive advantage.